Homology in Electromagnetic Boundary Value Problems. (1st August 2010) - Pellikka, Matti; Suuriniemi, Saku; Kettunen, Lauri
Abstract : We discuss how homology computation can be exploited in computational electromagnetism. We represent various cellular mesh reduction techniques, which enable the computation of generators of homology spaces in an acceptable time. Furthermore, we show how the generators can be used for setting up and analysis of an electromagnetic boundary value problem. The aim is to provide a rationale for homology computation in electromagnetic modeling software.